Factors contributing to and strategies for reducing Foreign Language Anxiety (FLA): A systematic literature review - Diah Palupi; Anita Triastuti; Sukarno; Ella Wulandari (Universitas Sarjanawiyata Tamansiswa, 2025)
Foreign Language Anxiety (FLA) is a significant obstacle influencing students’ academic performance and participation during the learning process. This paper aims to describe factors contributing to Foreign Language Anxiety (FLA) systematically and its strategies to reduce Foreign Language Anxiety (FLA) through a Systematic Literature Review approach of selected national and international literature (2015–2025). The findings showed that (1) psychological factors such as low self-confidence, fear of making mistakes, and fear of negative evaluation are major causes of FLA. Furthermore, linguistic limitations and sociocultural backgrounds also contributed to worsening students’ anxiety. (2) Coping strategies to overcome FLA are divided into two: individual strategies and instructional strategies. In addition, this paper also found that the relationship between the factors of FLA and coping strategies has rarely been investigated. Therefore, these findings are expected to be a reference for designing more adaptive and contextual English language learning in facing FLA.